Microglial subpopulations with distinct transcriptome signatures vary across brain regions in the resting mouse brain - Rei Mishima; Masayuki Taniguchi; Kazutoshi Matsushita; Bowen Tian; Tomoyuki Furuyashiki (Elsevier, 2023)
Microglia are crucial for tissue homeostasis and its disturbance. However, microglial heterogeneity and its relationship with microglial activation in physiological conditions remain elusive. Using single-cell RNA sequencing, we identified microglial subpopulations with distinct transcriptome signatures in the resting brain. The distribution of two major, continuous subpopulations varied across brain regions, especially between cerebral cortices and the hypothalamus. Lipopolysaccharide and chronic social defeat stress, both of which involve the innate immune receptor TLR4, upregulate the marker genes of selective microglial subpopulations. These findings suggest that microglial subpopulations contribute to the heterogeneity of microglial transcriptome and responsiveness within and across brain regions.